Assessment of Submarine Groundwater Discharge (SGD) as a Source of Nutrient at Jakarta Bay, Indonesia. Issue 1 (June 2021) - Lubis, R F; Bakti, H; Afdal,; Prayitno, H B; Bayhaqi, A; Onodera, S; Taniguchi, M
Abstract: Submarine groundwater discharge (SGD), the direct discharge of groundwater to the sea, is a ubiquitous phenomenon worldwide. While SGD is defined as "any and all flow of water on continental margins", this review focuses on the terrestrial fraction, also known as fresh SGD Jakarta Bay, which started from the late 1980s have had greatest impact on mangrove areas and coastal water quality due to the expanding of the city. In such an environment, inputs of nutrients will play an important role in sustaining primary productivity. Atmospheric deposition and riverine runoff have been traditionally considered the main external sources of nutrients to the bay, whereas the role of submarine groundwater discharge has been largely ignored. . In this study, we used radon tracers and salinity to investigate SGD and associated nutrient inputs to Jakarta Bay especially from Citarum Estuary as the main river. The result shows that SGD becomes an important role in understanding the nutrient cycle at Jakarta Bay.